Richard Guldeford's Pilgrimage: Piety and Cultural Change in Late Fifteenth‐ and Early Sixteenth‐Century England. Issue 329 (30th January 2013) - Lutton, Rob
Abstract The account of Sir Richard Guldeford's pilgrimage, printed in 1511, is just one of over 500 surviving medieval accounts of the Jerusalem pilgrimage. In many ways conventional, it nonetheless bears a number of distinctive features. Its presentation of first‐person detailed eyewitness testimony in conjunction with judicious use of source material, innovative treatment of travel balanced with sober and restrained piety, and eschewal of some of the more fabulous aspects of pilgrimage literature, all make it an important example of the vogue for sober piety in late fifteenth‐ and early sixteenth‐century England. It provides evidence of critical engagement with debates surrounding pilgrimage and related aspects of religious practice such as indulgences and the cult of relics, and it is an important example of new approaches to the writing and publishing of the literature of pilgrimage and travel. Richard Guldeford, royal courtier and civil servant, did not write the account of his pilgrimage to the Holy Land, but it emanated from the Guldeford family's interests in fashionable humanist learning and reformist religious sensibilities. The text's innovations and tensions are representative of wider shifts and deeper fault‐lines in late medieval religious culture prior to the enormous religious changes of the Reformation, and are further evidence of the ways in which pre‐Reformation orthodox religious culture was neither homogeneous nor unchanging. Above all, it offered a reformed and rehabilitated practice of the Jerusalem pilgrimage at a time when pilgrimage was increasingly vulnerable to attacks from both orthodox and heterodox critics.